PENGARUH IKLIM BELAJAR DI KELAS TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP N 2 SUNGAI PUA KABUPATEN AGAM - Nuraida Fatma; Puti Andam Dewi (CV. ADIBA AISHA AMIRA, 2025)
Achieving educational goals at school requires a learning climate that is conducive to participating in learning as part of the school education system. The school as an organization and educational institution whose components consist of students, educators and educational staff, requires a conducive atmosphere as a collective consistency that must be implemented, in order to realize the vision, mission and goals of education in schools. Likewise, students need a conducive learning atmosphere that reflects positive relationships between all elements of the school. Apart from that, the formulation of the problem in this research is: